Gain improvement in a dual-stage S-band EDFA by filtration of forward C-band ASE - Harun, Sulaiman Wadi; Zulkifli, Mohd Zamani; Tamjis, Mohamad Rom; Ahmad, Harith (Taylor & Francis, 2008)
Gain improvement in a dual-stage S-band erbium-doped fiber amplifier (S-band EDFA) is demonstrated using a broadband fiber Bragg grating (FBG) operating in the conventional-band (C-band) region or a C-band/S-band wavelength division multiplexing (WDM) coupler which filters out the forward C-band amplified spontaneous emission (ASE) in the amplifier system, thus increasing the population inversion in the S-band region. The gain for the amplifier with the WDM coupler increases by about 8.5 dB with an input signal power of 40 dBm, compared to that of the conventional dual-stage amplifier. The gain improvement varies from 4.0–9.2 dB at a wavelength region between 1480 to 1512 nm without a significant noise figure penalty.